Preparation of MC–CuS–PGr/PPy Nanocomposite Films via Strong Interfacial Interactions as a Battery‐Type Electrode. Issue 4 (3rd February 2022) - Gu, Sheng; Dong, Shu; Wang, Xue; Shi, Xiaolong; Xu, Guoqi; Wang, Lihai
Abstract : Flexible energy storage devices are an essential step towards the production of wearable and flexible electronic products. However, the design of flexible electrodes with excellent electrochemical performance still faces enormous challenges. This work reports a fabrication method for flexible electrodes. Specifically, the formation of MC‐CuS‐PGr/PPy nanocomposite films was driven by different interactions (including hydrogen bonds and π–π conjugated bonds). Nanocellulose@carbon nanotube (MC) acted as a flexible substrate and was encapsulated with polypyrrole (PPy), a hydrogen bond active site carrier. MC and PPy were interconnected through hydrogen bonds, and pencil graphite (PGr) was a secondary conductive network that served as a separating layer between CuS and PPy. Driven by the interaction, the nanocomposite film was a stable combination. The strong macromolecular interactions among MC, PPy, and PGr enhance conductivity and cycle life of this nanocomposite films. The water‐based hybrid cell was assembled based on an MC‐CuS‐PGr/PPy nanocomposite film, which exhibited high cyclability (capacity retention of 94.3% after 2000 cycles at 1 Ag −1 ) and provided an energy density of  Wh kg −1 (at a power density of 549.8 W kg −1 ). This research provides a new idea for preparing new flexible electrodes. Abstract : A battery‐type nanocomposite film driven by different intermolecular interactions is designed. Hydrogen bonds and π–π interactions interact synergistically to achieve a rapid combination of various materials and improve the structural stability, mechanical properties, and electrochemical performance of electrodes.